The private journal of Captain G.F. Lyon of H.M.S. Hecla during the recent voyage of discovery under Captain Parry [electronic resource]. - Lyon, G. F. (George Francis), 1795-1832 (London : J. Murray, 1824)
Electronic reproduction. Mode of access: Internet. 44